2003
DOI: 10.1044/1058-0360(2003/051)
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Subjective and Objective Measures of Tongue Strength and Oral Phase Swallowing Impairments

Abstract: A growing literature documents the relationship between tongue strength and oral phase swallowing function. Objective measures of strength have been recommended as more valid and reliable than subjective measures for the assessment of tongue function, yet subjective measures remain the more commonly used clinical method for assessing tongue strength. This study assessed the relationships among subjective and objective measures of tongue strength and oral phase swallowing impairments. Both subjective and object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
0
20

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(144 citation statements)
references
References 9 publications
11
109
0
20
Order By: Relevance
“…It is portable and easy to use, is noninvasive, and presents fast, accurate, and reliable measurements (4)(5)(6) . After that, many studies proposed to measure the pressure made by the tongue on the oral cavity (7) during functions such as speech (8) , swallowing, (5) and chewing (9) ; at rest (10) ; and during the maximum isometric contraction for comparing with different portions of the tongue (anterior and dorsum) among young adults (11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is portable and easy to use, is noninvasive, and presents fast, accurate, and reliable measurements (4)(5)(6) . After that, many studies proposed to measure the pressure made by the tongue on the oral cavity (7) during functions such as speech (8) , swallowing, (5) and chewing (9) ; at rest (10) ; and during the maximum isometric contraction for comparing with different portions of the tongue (anterior and dorsum) among young adults (11) .…”
Section: Introductionmentioning
confidence: 99%
“…It is portable and easy to use, is noninvasive, and presents fast, accurate, and reliable measurements (4)(5)(6) . After that, many studies proposed to measure the pressure made by the tongue on the oral cavity (7) during functions such as speech (8) , swallowing, (5) and chewing (9) ; at rest (10) ; and during the maximum isometric contraction for comparing with different portions of the tongue (anterior and dorsum) among young adults (11) . The pressure of the tongue has also been studied in relation to gender (11)(12)(13)(14) and age (5,(13)(14)(15) in individuals diagnosed with obstructive sleep apnea (16) , neurological conditions (17) , and disorders in the head and neck area (18) .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found greater force in men (2,6,13,(15)(16)(17) . However, in other studies such difference was not observed (12,14,(18)(19)(20)(21)(22) . The influence of weight, height and body mass index (BMI) on tongue strength has been little studied.…”
Section: Introductionmentioning
confidence: 72%
“…Renata Maria Moreira Moraes Furlan (1) , Amanda Freitas Valentim (2) , Andréa Rodrigues Motta (3) , Márcio Falcão Santos Barroso (4) , Cláudio Gomes da Costa (5) , Estevam Barbosa de Las Casas (6) …”
Section: Quantitative Methods For Assessing Tongue Forceunclassified
“…(2) Fonoaudióloga; Mestranda em Bioengenharia pelo Programa de Pós Graduação em Engenharia Mecânica da Universidade Federal de Minas Gerais -UFMG, Belo Horizonte, Minas Gerais, Brasil. Engenheiro; Professor Adjunto do Departamento de Engenharia Elétrica da Universidade Federal de São João del-Rei -UFSJ, São João del-Rei, Minas Gerais, Brasil; Doutor em Engenharia Elétrica pela Universidade Federal de Minas Gerais.…”
Section: Descritoresunclassified